Proceedings of the Workshop on Large Language Models for Research Data Management?! (LLMs4RDM 2025) co-located with the INFORMATIK Festival 2025 (55th Annual Conference of the German Informatics Society). Potsdam, Germany, September 18, 2025 - Bender, Magnus [Herausgeber]; Melzer, Sylvia [Herausgeber]; Möller, Ralf [Herausgeber]; Thiemann, Stefan [Herausgeber] (My University, 2025)
"The rapid rise of large language models (LLMs) has opened new possibilities for research across the humanities, transforming how scholars analyse texts, interpret complex datasets, and engage with cultural, linguistic and historical materials. While these technologies promise powerful new methods of discovery, they also bring conceptual, methodological and ethical challenges that humanities researchers are only beginning to explore. The first Workshop on Large Language Models for the Humanities?! (LLMs4RDM) was created as a forum to address these emerging opportunities and questions. Bringing together researchers, practitioners and infrastructure specialists, the workshop aims to foster dialogue on how LLMs can be meaningfully integrated into research workflows, from data creation and curation to analysis, interpretation and communication. By examining both the potential and the limitations of these models, the workshop seeks to support a more informed, critical and creative engagement with LLMs. One keynote and five papers were presented at the workshop." (Editors' abstract, BIBB-Doku)
Keywords: T 3 Forschungsmethoden; G 2.2.1 Technologisierung; 370; 600; Forschungsdaten; Large Language Model; Datenanalyse; Künstliche Intelligenz